The Effectiveness of Using Role Play in Conducting Programming Classes - Chen, Lim Fung; Yee, Haw Wai (International Journal of Asian Social Science, 2013)
It is always a challenge to a lecturer to obtain undivided attention from a programming lab class. Conventional lecture and lab sessions are not effective enough in the delivery of programming knowledge. Role play allows students actively involved in the class activities. Via the role assigned; the student is having a better understanding of the knowledge delivered to them. This paper performs a study on the application of role play in teaching parameter-passing of C programming language. Based on the observation during and after the class, it shows that role play do have a significant effect in conducting programming classes.